Numerical Analysis of Continuous Dieless Wire Drawing Process - Jabbar Mohammed, Rafid; Khalaf Ali, Jaafar; Ahmed Nassar, Ameen (International Journal of Engineering and Technology, 2018)
Dieless wire/tube drawing process is a novel technique has been developed in the past four decades utilizing super plasticity phenomenon, in which, the wire/tube is locally heated to a specified temperature and then subsequently locally cooled so as to further deformation is suppressed. This process is carried out without using the conventional drawing dies. A stainless steel SUS304 wire, 2mm diameter was used in this analysis. A coupled thermo-mechanical model has been developed and verified numerically. The thermal model was constructed to predict the temperature profile longitudinally along z-axis. As soon as the temperature distribution is obtained then the mechanical model was ready to predict the radius profile of the wire until the desired radius after deformation is satisfied. The effects of feeding velocity of the wire, heating coil length, cooling nozzle diameter, the distance between heating and cooling coils and redial distance which is affected by cooling air on temperature and radius profiles of the wire were considered here. Also, a symmetrical and asymmetrical distribution of the heat transfer coefficient for the wire cooling was also proposed in this study. The results showed that above parameters had important effects on temperature distribution and thus on radius profile of the drawn wire. Moreover, the symmetrical mode of heat transfer coefficient led to more stable for the temperature profile than asymmetrical mode. Consequently, to achieve more stability of this process, the above parameters must be determined accurately.Â Â Â